Design and implementation of a knowledge base for the office of the Vice Mayor Of Marikina City’s COVID-19 effort - Santos, Patcheska Dewi R.
Knowledge bases are used for different purposes, depending on the information needs and system that will best suit an institution. For this project, the system will solely focus the COVID-19 pandemic efforts of the OVM that will be deemed needed for a knowledge base. Interviews with the stakeholders were conducted in order to understand the records processes as well as to gather data to figure out how the OVM knowledge base will be designed and developed. Knowing the stakeholders as well as their participation in the project is necessary as this also indicates the requirements that the project manager must meet and strategies to be done.